Of form and feeling: correlating urban form and feelings of insecurity in Porto, Portugal - Saraiva, Miguel Marinho (2022)
Environmental criminology is built on the principle that criminal behaviour is conditioned by the (built) environment it occurs in, and that the introduction/removal of design and built features may reduce insecurity and criminal occurrences. Hence, local-based strategies have proven that "place matters" in crime-prevention, and have established the need for interdisciplinary research where urban morphology plays a central role, due to the influence of different spatial elements in feelings and behaviours. Although environmental criminology exists since the 1970s, it has recently been the object of new interest due to the increased success of strategies related to the criminology of places. This paper pretends to contribute to this debate by making an early exploration of how different components of place (built environment) and safety (perceptions of insecurity) correlate, using the city of Porto as case study. Based on a population survey carried out in 2020, feelings of unsafety towards places and their environmental features were determined, and compared with morphological variables at local level, derived from official data sources. A sample of about 500 respondents was analysed, and the results were compared spatially. It is expected that the resulting research contributes to draw locallybased prevention strategies based on the articulation between urban morphological elements, planning policies and the different realms of prevention.